Lenvatinib in advanced radioiodine-refractory differentiated thyroid cancer: what’s new? - E. V. Borodavina; S. I. Kutukova; A. Yu. Shurinov; V. V. Krylov (Опухоли головы и шеи)
The article provides the latest data of our foreign colleagues on the potential use and dosing regimen of lenvatinib in real clinical practice. Since adverse events during lenvatinib treatment often lead to dose reduction or its discontinuation and, as a consequence, to a decrease in progression-free survival and overall survival benefit, optimization of lenvatinib dosing regimen is of great interest to experts from different countries. Today, so-called drug holidays are being actively studied as a possible option to reduce lenvatinib toxicity, without loss of efficacy in patients with advanced radioiodine-refractory differentiated thyroid cancer. In addition, given the small number of therapeutic options for this patient group, their low efficacy and poor availability of tumor mutation profiling and effect on target genes, a question arises: “Is it possible to benefit in progression-free survival and overall survival with lenvatinib rechallenge after disease progression in the 2nd or 3rd treatment lines?”